PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP HARGA SAHAM PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wulandari, Erida Sri; Widarno, Bambang; Kristanto, Djoko (Universitas Slamet Riyadi, 2020)
The financial performance of the company in this study is represented by Current Ratio (CR), Debt To Equity Ratio (DER), Return On Equity (ROE) and Total Assets Turnover (TATO). This study aims to determine the effect of these four variables on stock prices in property and real estate companies listed on the IDX. Sample selection using purposive sampling technique and obtained a sample of 15 companies.The technique of data analysis done with the classical assumption and multiple linear regression, hypothesis testing using t test, F test and coefficient of determination test using SPSS 25 for windows. The results showed that Current Ratio, Debt To Equity Ratio, Return On Equity and Total Assets Turnover simultaneously have sicnificant effect on stock prices, for partial research the results indicate that the variable Current Ratio, Debt to Equity Ratio, and Total Asset Turnover has no significant effect on stock price.